COCONUT LEAF ROT DISEASE COMPLEX A REVIEW - N. Srinivasan; M Gunasekaran (International Coconut Community, 1999)
Occurrence of leaf rot disease (LRDC) of coconut is related to increased incidence of root wilt disease (RWD). The palms with RWD irrespective of age are susceptible, young ones are more susceptible to LRDC. Tender leaves especially the spindle play a critical role in LRDC incidence and the disease attributed to fungal complex. Among the 14 species of LRDC Angi, several were proved to be pathogenic; Colletotrichum gloeosporioides (Penzig) Penzig and Sacc and Exserohilum rostratum (Drechsler) Leonard and Suggs are discerned as the main pathogens. C. gloesporoides was aggressive during monsoons and positively correlated with rainfall and relative humidity (11% RH, whereas Erostratum less strongly correlated Fusarium spp. predominated in dry seasons. Importance of microclimate, survival and quiescence of the pathogens are to be determined. Diagnosis of RWD by techniques such as PCR and understanding the molecular basis of vulnerability of palms to LRDC would help to initiate early control measures. Planting of RWD cum LRDC resistantl tolerant varieties after eradicating the RWD infected palms is desirable. Protection ofyoung leaves by chemical or biocontrol agents or a combination of both with phytosanitation is important. 4 system approach with integrated measures needs to be utilizedfor sound management of LRDC.